PENGEMBANGAN MODUL PEMBELAJARAN MENULIS IKLAN LAYANAN MASYARAKAT DI SMP BERBASIS PENDEKATAN SAINTIFIK - Diah Ayu; Bambang Riadi; Rahmat Prayogi (FKIP Universitas Lampung, 2021)
This research was conducted with the aim of developing products in the form of a learning module for Writing Public Service Advertisements in Junior High Schools, as well as describing the feasibility of the module. This research used Research and Development (R D) method which referred to Borg Gall’s design. Data collecting techniques using an interview with Indonesian language educator and the validation questionnaires by educator and material expert. The results of this research indicated that The results of this study indicated that the feasibility based on material expert validation on the aspects assessed obtained an average score of 4.4 and an average percentage of 87.5% with very decent criteria. The results of validation by Indonesian language educators on the assessed aspects obtained an average score of 4.6 and an average percentage of 92.8% with very decent criteria. Based on the results of the validation of material experts and educators, the learning module developed is declared suitable for use.Penelitian bertujuan untuk mengembangkan produk berupa modul pembelajaran Menulis Iklan Layanan Masyarakat di SMP, serta mendeskripsikan kelayakan modul tersebut. Penelitian ini menggunakan metode Research and Development (R D) yang merujuk pada model Borg Gall. Teknik pengumpulan data menggunakan wawancara pada pendidik bahasa Indonesia dan angket validasi oleh pendidik dan ahli materi. Hasil penelitian ini menunjukkan bahwa kelayakan berdasakarkan validasi oleh ahli materi terhadap aspek-aspekyang dinilai diperoleh skor rata-rata 4,4 dan rerata presentase 87,5% dengan kriteria sangat layak. Hasil validasi oleh pendidik bahasa Indonesia terhadap aspek-aspek yang dinilai diperoleh skor rata-rata 4,6 dan rerata presentase 92,8% dengan kriteria sangat layak. Berdasarkan hasil validasi ahli materi dan pendidik maka modul pembelajaran yang dikembangan dinyatakan layak digunakan.Keywords: module, public service advertisement, scientific approach.DOI: http://dx.doi.org/10.23960/Kata.v9.i2.202104